Technologies of Power and Expressionism: Reading Demetrio Aguilera Malta in the Key of Science Fiction - Rodrigo-Mendizábal, Iván Fernando (2023)
Starting from the idea that all technologies of power, according to Michel Foucault, determine the behavior of individuals, objectifying them, and, also considering the position that the Ecuadorian writer Demetrio Aguilera Malta adopts, in the context of expressionism, an aesthetic that exposes and appeals to the sensitive in conflict with what the being lives before its dehumanization, a group of his works is analyzed from the perspective of science fiction. Indeed, Aguilera Malta is an author who, hybridizing narrative genres, is the one who ventures to introduce elements of science fiction in certain works, some theatrical and others novel, in order to expose his concerns about the middle of the century, when the human being has witnessed a techno-scientific degradation whose culminating point is the detonation of the atomic bomb. The article places the pessimistic or disenchanted speech of Todos los átomos (1955), by Muerte S.A. (1970) and Infierno negro (1970), as founders of the Ecuadorianscience fiction theater; and he contrasts them with the novels El secuestro del general (1973) and Réquiem para el diablo (1978) which denote his concern about how power technologies serve to subdue.